Severe visual loss from concurrent fulminant idiopathic intracranial hypertension and malignant arterial hypertension: Prompt suspicion matters - Bashaer Aldhahwani; Serena M. Shah; Hong Jiang; Byron L. Lam (American Journal of Ophthalmology Case Reports)
Purpose: To report a case series of 4 patients with poor visual outcomes from concurrent fulminant idiopathic intracranial hypertension (IIH) and malignant arterial hypertension with bilateral optic disc edema. The diagnosis of fulminant IIH was delayed given the bilateral optic disc edema was attributed initially to hypertensive optic neuropathy. Observation: All 4 patients (3 males, 3 African Americans, mean BMI 27.6 kg/m2 (range 19.5–36 kg/m2) presented to the emergency department with bilateral vision loss, optic disc edema, and blood pressure (BP) of greater than 180/120. The patients were treated initially to control BP and the optic disc edema was either attributed to the hypertension or the ophthalmic examination was not performed. The patients were subsequently diagnosed with IIH with Brain MRI, MR venogram, and lumber puncture (mean cerebrospinal fluid (CSF) opening pressure 42 cm, range 40–43 cm). The mean time from presentation to diagnosis of IIH was 3.2 months (range 1–6 months). The final visual acuity ranged from 20/400 to hand motions in the better eye and count fingers to hand motions in the worse eye despite bilateral optic nerve sheath fenestrations (3 patients), ventriculoperitoneal shunts (3 patients), and treatments with acetazolamide (3 patients) and furosemide (1 patient). Conclusion: Our case series underscores the need to promptly include IIH in the differential diagnosis in patients with bilateral optic disc edema including patients with malignant hypertension, particularly in those experiencing progressive visual loss, regardless of gender or BMI. Prompt work-up with brain MRI with contrast and MR or CT venogram to detect neuroimaging signs of intracranial hypertension followed by a lumbar puncture with CSF opening pressure are essential to initiate rapid treatment of fulminant IIH to avoid poor outcome.